The Experiences of School Counselors as Antibullying Specialists: A Phenomenological Study. (January 2019) - Hannon, Michael D.; Sheely-Moore, Angela I.; Conklin, Thomas; Reitter, Andrew J.; Gainor, Kathy A.
To learn about school counselors' experiences in being assigned as their school's antibullying specialist (ABS), per state legislation, we interviewed six school counselors and analyzed their responses using interpretative phenomenological design. The participants' responses reflected three overarching themes describing their ABS experience: negotiating different bullying definitions, the "dumping ground" position, and inherent with role conflicts. We present implications for school counseling practice and recommendations for school counseling research.